After Sales Service Quality on Customer Satisfaction and Retention among Game Store Customer's in Kano State, Nigeria - Abdullahi, Mohammed Sani; Shehu, Ummi Rahma; Usman, Bashir Mikail; Muhammad, Yusuf Suleiman; Kano, Aisha Hamisu (International Journal of Business Strategy and Social Sciences, 2019)
This research examines the effect of after sales service quality (ASSQ) on customer satisfaction (CS) and customer retention (CR) among Game store customer’s in Kano State, Nigeria. The population was 870 Game store after-sales service (ASS) customers who received after-sales service (ASS) multiple times. Simple random technique was used that allow the researchers to assess their study's centered participants, and the main tools used for this study were questionnaires. The questionnaire was intended to a Likert scale of 10 points, with the assistance of 3 ASS technician and 3 foremen at Game Store Kano, the information were gathered from 255 ASS customers. The study's hypothesized model was tested using Structural Equation Modelling (SEM). The research outcomes show that ASSQ has a substantial and positive effect on CS and CR. The outcome also shows that CS has substantial and positive effect on CR. It is suggested that businesses or organizations should explore the most significant dimensions of ASSQ to match the preferences of their customer’s with that the organizations will pays a lot of attention to their esteem customer’s, and it will assist businesses achieve their mission and vision.